INDONESIAN LANGUAGE ASSISTANT PROGRAM IN AUSTRALIAN SCHOOLS: RECRUITMENT AND SELECTION PROCESS - Tri Indri Hardini; Sri Setyarini; Sri Harto (Jurnal Cakrawala Pendidikan, 2019)
This research aims to investigate the process of recruitment, selection, and implementation of the Indonesian language assistant program of the Universitas Pendidikan Indonesia (UPI) in Australian schools. The main purpose of this research is to find out the processing stages and to see strengths and weaknesses in each stage of the recruitment and selection process held at UPI. The data were collected through survey questionnaires, in-depth interviews, and documents of the Indonesian language assistants on the implementation of the program. The questionnaires and interviews were directed to the members of recruitment and selection team, alumni, and candidates of the Indonesian language assistants. A descriptive qualitative method was applied to explore and analyze the activities of the language assistants’ candidates and alumni in each of the overall stage processes. The results show that there are some stages of recruitment and selection process, which are then described in a figural process. The recruitment covered the submission of a curriculum vitae completed by relevant administrative documents to qualify for registering the program. The selection process required skills and competences of the candidates in Indonesian language, English, Indonesian and Australian cultural knowledge and skills and self-management. Accordingly, a system development for recruitment and selection process to result in more competent candidates for the Indonesian language assistants is urgently needed to elaborate the whole process in efficient manner.